Prevalence of non-communicable diseases among healthy male decontamination workers after the Fukushima nuclear disaster in Japan: an observational study - Toyoaki Sawano (Nature Portfolio, 2021)
Abstract The health status of healthy decontamination workers employed after the Fukushima nuclear disaster remains unclear. This study aimed to evaluate the prevalence of non-communicable diseases among such workers. In this observational study, questionnaires on lifestyle and social factors were administered as part of a health promotion program for decontamination workers in 2016 in Minamisoma City, Fukushima. The questionnaires and health check-up results were compared with those of the 2016 National Health and Nutrition Examination Survey (NHANES) in Japan. Overall, 123 male decontamination workers were enrolled; 93 (75.6%) were drinkers, and 84 (68.3%) were current smokers. The age-adjusted prevalence (95% confidence interval) of hypertension, dyslipidemia, diabetes mellitus, and obesity were 27.2% (20.1–34.4%), 30.4% (22.6–38.2%), 11.3% (5.5–17.1%), and 49.0% (39.0–58.9%), respectively. The age-adjusted prevalence in the NHANES were 32.8% (31.1–34.5%), 16.1% (14.5–17.6%), 7.0% (6.2–7.7%), and 31.2% (29.9–32.5%), respectively. The prevalence of obesity, dyslipidemia, binge drinking, and smoking were higher in healthy male decontamination workers than in the general population. Decontamination workers in disaster-struck areas may have higher risks of developing non-communicable diseases, possibly due to their original health status. Continuous monitoring of their health status and proper interventions are warranted.